Identification and validation of CDK1 as a promising therapeutic target for Eriocitrin in colorectal cancer: a combined bioinformatics and experimental approach - Jiemiao Shen; Xing Gong; Haili Ren; Xia Tang; Hairong Yu; Yilu Tang; Shen Chen; Minghui Ji (BMC Cancer)
Abstract Background Colorectal cancer (CRC) is a prevalent malignancy worldwide, associated with significant morbidity and mortality. Cyclin-dependent kinase 1 (CDK1) plays a crucial role in cell cycle regulation and has been implicated in various cancers. This study aimed to evaluate the prognostic value of CDK1 in CRC and to identify traditional Chinese medicines (TCM) that can target CDK1 as potential treatments for CRC. Methods The expression and prognostic value of CDK1 were analyzed through TCGA, GEO, GEPIA, UALCAN and HPA databases. An ESTIMATE analysis was applied to estimate the proportions of stromal and immune cells in tumor samples. GO and KEGG enrichment analyses were performed to clarify the functional roles of CDK1-related genes. CCK-8, colony formation, cell migration, cell invasion, and wound healing assays were employed to explore tumor-promoting role of CDK1. Molecular docking, cellular thermal shift, and isothermal dose-response assays were employed to identify potential inhibitors of CDK1. Results CDK1 was highly expressed in CRC and associated with a poorer prognosis. The expression of CDK1 was also correlated with the levels of immune cells infiltration. CDK1-related genes were primarily involved in the cell cycle and the P53 signaling pathway. Knockdown of CDK1 inhibited the proliferation, migration, and invasion of CRC cells in vitro. Furthermore, Eriocitrin emerged as a potential inhibitor, exerting its anti-tumor effects by targeting and inhibiting CDK1 activity. Conclusion CDK1 plays a critical role in CRC prognosis. Eriocitrin, a potential CDK1 inhibitor derived from TCM, highlights a promising new therapeutic strategy for CRC treatment.